Developing operational environments and educational activities for early childhood development students in museums. (2nd January 2022) - Chitima, Simbarashe Shadreck
ABSTRACT: National museums in Zimbabwe receive Early Childhood Development students (ECDs), but very little is known about how they find museums educationally worthy. This study examines the suitability of museum environments and educational activities in facilitating the learning of curriculum content among ECDs. This study employed qualitative research and multiple case studies. Interviews, observations, focus group discussions and listening to ECDs conversations were employed as research instruments. The research population included 800 ECDs, 200 ECDs teachers, 31 museum tour guides, 7 curators and 4 museum education officers. The study was undertaken from 2010 to 2019 at five national museums in Zimbabwe. It is revealed that national museums in Zimbabwe have few child-sized facilities, environments and educational programmes for ECDs. Therefore, ECDs face physical, attitudinal and intellectual barriers in accessing museums. It is concluded that national museums in Zimbabwe consider ECDs a postscript hence students and teachers treat museum excursions as leisure outings.